2020
DOI: 10.1007/s12072-020-10071-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease (COVID-19) and the liver: a comprehensive systematic review and meta-analysis

Abstract: Background Liver function derangements have been reported in coronavirus disease (COVID-19), but reported rates are variable. Methods We searched PubMed and Embase with terms COVID and SARS-COV-2 from December 1, 2019 till April 5, 2020. We estimated overall prevalence, stratified prevalence based on severity, estimated risk ratio (RR), and estimated standardized mean difference (SMD) of liver function parameters in severe as compared to non-severe COVID. Random effect method utilizing inverse variance approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 21 publications
6
141
1
10
Order By: Relevance
“…Further on, in a recently published letter on the involvement of the liver in COVID-19, the authors found an increased odds of severe infection and mortality in patients with liver injury (71). Another study analyzed the frequency of abnormal liver function derangements in severe COVID-19 and concluded that hypoalbuminemia followed by derangements in GGT and aminotransferases were more frequent in severe disease (72). On the other hand, another study highlights that digestive symptoms and liver injury are not uncommon in patients with SARS-CoV-2 infection (73).…”
Section: Discussionmentioning
confidence: 99%
“…Further on, in a recently published letter on the involvement of the liver in COVID-19, the authors found an increased odds of severe infection and mortality in patients with liver injury (71). Another study analyzed the frequency of abnormal liver function derangements in severe COVID-19 and concluded that hypoalbuminemia followed by derangements in GGT and aminotransferases were more frequent in severe disease (72). On the other hand, another study highlights that digestive symptoms and liver injury are not uncommon in patients with SARS-CoV-2 infection (73).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that 11 of 96 asymptomatic patients developed symptoms, and it was suggested that this could occur more with increasing age. 17 Kumar et al 18 showed the most frequent abnormality in liver functions was hypoalbuminemia, followed by derangements in gamma-glutamyl transferase and aminotransferases, and these abnormalities were more frequent in severe disease. 18 The results were the same in our study.…”
Section: Discussionmentioning
confidence: 99%
“…17 Kumar et al 18 showed the most frequent abnormality in liver functions was hypoalbuminemia, followed by derangements in gamma-glutamyl transferase and aminotransferases, and these abnormalities were more frequent in severe disease. 18 The results were the same in our study. The consensus is lacking for this group of patients; few have suggested close monitoring, while others in favor of early antiviral therapy to prevent prolong shedding.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of elevated liver transaminases (ALT and AST) in COVID-19 patients ranges from 2.5% to 76.3%. 35,38,43,44 In a recent meta-analysis, the pooled rate for AST and ALT outside the reference range was 20%-22.5% and 14.6%-20.1% respectively. 35,45 These abnormalities can be accompanied by slightly increased total bilirubin levels in up to 35% of cases.…”
Section: The S Pec Trum Of Liver Involvement In Covid -19mentioning
confidence: 99%
“…35,45 These abnormalities can be accompanied by slightly increased total bilirubin levels in up to 35% of cases. 35,38,43,44 While elevations of cholestatic liver enzymes [alkaline phosphatase (ALP) and gamma glutamyl transferase (γGT)] were initially considered rather rare, 4,22,23,46 recent systemic reviews highlight elevations of ALP and γGT in 6.1% and 21.1% of COVID-19 patients respectively. 35,45 Moreover, a biphasic pattern with initial transaminase elevations followed by cholestatic liver enzymes has been reported, which could reflect SIRS-induced cholestasis at the hepatocellular/canalicular level or more severe bile duct injury in the later stage of the disease.…”
Section: The S Pec Trum Of Liver Involvement In Covid -19mentioning
confidence: 99%